Perbedaan Efektivitas Terapi Betahistin Dan Kombinasi Dengan Difenhidramin Pada Pasien Vertigo Perifer Di RSUD Sukoharjo - Febriyanto, Danu Ihyar, dr. Ani Rusnani Fibriani, Sp.S, dr. Budi Hernawan (2015)
Background : Peripheral vertigo is a disorder of the form orientation a perceived space around rotating or moving on him, usually accompanied by nausea, vomiting. In Indonesia, the incidence of vertigo is very high, in 2010 from age 40 to 50 years around 50%. Use of Betahistine for peripheral vertigo in Europe is quite high, it is different with the use of a combination of diphenhydramine. Objective : To determine the effectiveness of betahistine and combination with diphenhydramine against peripheral vertigo in Sukoharjo Hospital.Methods : This study uses observational analytic design with cross sectional approach to patients peripheral vertigo in Sukoharjo hospital. Results : Based on analysis result of data using chi-square test was obtained p = 0.317 (p <0.05). Conclusion : There are no significant differences between Betahistine therapy and combination with diphenhydramine in the treatment of patients peripheral vertigo in Sukoharjo hospital.